AGRONOMIC PERFORMANCE OF CORN IN FUNCTION OF METHODS OF APPLICATION AND DOSES INOCULATED WITH Azospirillum brasilense - FIORINI, IVAN VILELA ANDRADE; TONIAL, MAURÍCIO ESCOBAR; PEREIRA, CASSIANO SPAZIANI; SABINO, DANIELE CRISTINA COSTA; DIAS, IARA GARCÊS; TACCA, JULIO GUILHERME; SCHOFFEN, MATEUS EMANUEL (REVISTA BRASILEIRA DE MILHO E SORGO, 2020)
Nitrogen supplementation becomes necessary when trying to increase yields of off-season corn crop grown in rotation with early-maturing soybean crop. Biological nitrogen fixation helps reduce the use of nitrogen fertilizers through the inoculation of nitrogen-fixing associative bacteria, such as those of the genus Azospirillum. This study aimed to evaluate the agronomic performance of corn hybrid DKB390Y in response to different application methods as the inoculant and doses of inoculant with Azospirillum brasiliense. The experiment was conducted in a property adjacent to Federal University of Mato Grosso (Sinop campus), between February and July 2018. The experimental design included randomized blocks in a 3×5 factorial arrangement, replicated four times, thereby totaling 60 plots (with three application methods: foliar spraying, spraying foliar with bovine gelatin, and with a paint roller [Black & Decker Rapid Roller BDPR400-wool] and five doses of inoculant: 0, 100, 200, 400 and 800 mL ha-1). No differences in chlorophyll content at the bottom of the plant, plant height, and leaf area index were observed when varying the application methods. However, leaf nitrogen level, dry mass and grain yield changed when the application method used for inoculation changed. When evaluating doses, the control was found to be superior to the other treatments based on chlorophyll content at the bottom of the plant, plant height,leaf area, leaf nitrogen, and dry mass values. Grain yield was found to be superior with foliar inoculation at 100 mL ha-1 method foliar spray and 200 mL ha-1 methods foliar application with bovine gelatin.